Metabolomic Investigation of Ultraviolet Ray-Inactivated White Spot Syndrome Virus-Induced Trained Immunity in Marsupenaeus japonicus - Zang, Shaoqing; Lv, Li-Xia; Liu, Chen-Fei; Zhang, Peng; Li, Cang; Wang, Jin-Xing (Frontiers in Immunology, 2022)
Trained immunity is driven by metabolism and epigenetics in innate immune cells in mammals. The phenomenon of trained immunity has been identified in invertebrates, including shrimp, but the underlying mechanisms remain unclear. To elucidate mechanisms of trained immunity in shrimp, the metabolomic changes in hemolymph of Marsupenaeus japonicus trained by the UV-inactivated white spot syndrome virus (UV-WSSV) were analyzed using tandem gas chromatography–mass/mass spectrometry. The metabolomic profiles of shrimp trained with UV-WSSV followed WSSV infection showed significant differences comparison with the control groups, PBS injection followed WSSV infection. 16 differential metabolites in total of 154 metabolites were identified, including D-fructose-6-phosphate, D-glucose-6-phosphate, and D-fructose-6-phosphate, and metabolic pathways, glycolysis, pentose phosphate pathway, and AMPK signaling pathway were enriched in the UV-WSSV trained groups. Further study found that histone monomethylation and trimethylation at H3K4 (H3K4me1 and H3K4me3) were involved in the trained immunity. Our data suggest that the UV-WSSV induced trained immunity leads to metabolism reprogramming in the shrimp and provide insights for WSSV control in shrimp aquaculture.